ANALISIS KEMAMPUAN PEMECAHAN MASALAH PADA SOAL CERITA MATEMATIKA BERDASARKAN TEORI POLYA DITINJAU DARI ADVERSITY QUOTIENT - Novita Nurul Aini; Mohammad Mukhlis (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
One of the studen learning goals mathematics is mathematical reasoning for outcomes training student to solve the problems. One of the problems faced by students is word questions. There are several students responses in dealing with word question which is known as Adversity Quotient. This research aims to describe the students' problem solving skills in system of three-variable linear equations subject based on Polya's theory in terms of Adversity Quotient. This is a qualitative descriptive research with three subjects of students class X IPA 1 SMAN Arjasa Jember, there are one climber student, one camper student and one quitter student. These subjects took purposive sampling with consideration according to the results of questionnaire scores that meet each of the criteria of Adversity Quotient. Data collection techniques used were questionnaires, tests, interviews and observations. The validity test used is technical triangulation. Data analyzed through data condensation, data presentation and conclusion drawing. The results showed that student with the type of climber was able to meet all the indicators of problem solving in the problem of the word questions which included indicators of understanding the problem, planning the solution, carrying out the plan of solving and re-checking. Camper type student met all indicators of problem solving except at the re-checking stage. Quitter type student in completing word questions met the stage of understanding the problem and planning the solution, while the stage of carrying out the plan and re-checking is not fulfilled by the quitter student.